2019
DOI: 10.3389/fpsyg.2019.00989
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Inflexibility Predicts Extremist Attitudes

Abstract: Research into the roots of ideological extremism has traditionally focused on the social, economic, and demographic factors that make people vulnerable to adopting hostile attitudes toward outgroups. However, there is insufficient empirical work on individual differences in implicit cognition and information processing styles that amplify an individual’s susceptibility to endorsing violence to protect an ideological cause or group. Here we present original evidence that objectively assessed cognitive inflexibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 70 publications
4
85
0
2
Order By: Relevance
“…On a societal level, such skewed information intake might lead to entrenched beliefs, and, in turn, the prevalence of dogmatic groupings and widespread polarization (Zmigrod, 2020;Rollwage et al, 2019). In line with this hypothesis, people who show a resistance to belief updating are also more likely to show extreme political beliefs (Zmigrod, Rentfrow, et al, 2019b), aggression towards opposing political views (Zmigrod, Rentfrow, et al, 2019a), and authoritarian (Sinclair et al, 2019) or dogmatic traits (Rollwage et al, 2018;Zmigrod, Zmigrod, et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
“…On a societal level, such skewed information intake might lead to entrenched beliefs, and, in turn, the prevalence of dogmatic groupings and widespread polarization (Zmigrod, 2020;Rollwage et al, 2019). In line with this hypothesis, people who show a resistance to belief updating are also more likely to show extreme political beliefs (Zmigrod, Rentfrow, et al, 2019b), aggression towards opposing political views (Zmigrod, Rentfrow, et al, 2019a), and authoritarian (Sinclair et al, 2019) or dogmatic traits (Rollwage et al, 2018;Zmigrod, Zmigrod, et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
“…Carnes and Lickel's (2018) manifest that perceiving that the group shares core moral beliefs or convictions can also cause fusion. Finally, Zmigrod, Rentfrow, and Robbins (2018, 2019) found evidence that cognitive inflexibility and ideological orientations could shape our personal sense of nationalistic identity, bolstering fusion with national groups.…”
Section: Main Advances and Discoveries Since 2015 For Identity Fusionmentioning
confidence: 99%
“…Evidence for the neurocognitive antecedents and consequences of ideologies can be found in the burgeoning fields of political neuroscience and experimental social psychology. Recent work has revealed that ideologically-neutral cognitive and perceptual decision-making processes are related to higher-level ideological convictions and beliefs (Rollwage, Dolan, & Fleming, 2018;Rollwage, Zmigrod, De-Wit, Dolan, & Fleming, 2019;Zmigrod et al, 2018aZmigrod et al, , 2018bZmigrod et al, , 2019aZmigrod et al, , 2019bZmigrod et al, , 2019cZmigrod, 2020). Three cognitive traits that have been recently shown to confer susceptibility to ideological thinking are particularly noteworthy: (a) cognitive inflexibility, (b) impaired metacognitive awareness, and (c) slower perceptual evidence accumulation processing.…”
Section: Empirical Support For the Neurocognitive Modelmentioning
confidence: 99%
“…Firstly, there is evidence that a tendency towards mental rigidity can foster ideological rigidity. Cognitive inflexibilityoperationalized as a difficulty with switching between modes of thinking and adapting to changing environmental contingencieshas been implicated in extreme ideological identities (for review see Zmigrod, 2020) in the context of politics (Zmigrod et al, 2020), nationalism (Zmigrod, Rentfrow & Robbins, 2018), religion (Zmigrod et al, 2019a), dogmatism (Zmigrod et al, 2019c), and a willingness to endorse violence and self-sacrifice (Zmigrod et al, 2019b). In these studies, cognitive inflexibility was measured with objective behavioural tests of executive function and perception, and so the findings are not susceptible to the problems of self-report personality surveys in which there can be biases of social-desirability, self-perception, and social norms.…”
Section: Empirical Support For the Neurocognitive Modelmentioning
confidence: 99%